Comparison of single bacteria and a bacterial reference community in a test against coated surfaces of varying copper content - Ly-Sauerbrey, Yen; Anton, Ronja; Kopruch, Laura; Krämer, Carolin Luisa; Boschert, Alessa L.; Neidhöfer, Claudio; Schwengers, Oliver; Zander, Daniela; Leuko, Stefan (Frontiers in Microbiology, 2025)
IntroductionPathogens can easily transmit via surfaces and objects. In light of the ongoing pandemic of antimicrobial resistance, silently threatening millions worldwide, this is of particular concern in clinical and public environments. Thus, it is crucial to understand how antimicrobial materials influence surface-associated microbes and microbial communities. Copper, known for its antimicrobial activity, has demonstrated effectiveness against numerous clinically relevant pathogens. However, these in vitro pure cultures are in stark contrast to the in vivo microbial communities. Additionally, the application of pure copper surfaces is high in cost and maintenance.MethodsHence, in this study we not only tested the antibacterial effectivity of different copper concentrations against single species, but also against a reference bacterial community representing the most abundant bacterial genera in public transport. This allowed a comparison of the antibacterial efficacy of copper against a bacterial community and against single species. Coatings on glass, which were composed of full copper (100 at.% Cu) and copper-aluminum alloys with different Cu contents (79 at.%, 53 at.% and 24 at.%) were tested with two selected single species (Burkholderia lata DSM 23089T and Staphylococcus capitis DSM 111179) and those species within the bacterial community.ResultsIn general, the survival of the two species within the bacterial community was higher compared to their respective survival as a single species, significantly for S. capitis. Surfaces with 100 at.% copper content showed the greatest antibacterial effect in terms of bacterial survival, with a reduced survival of up to 10−6. The 79 at.% Cu coating only had an inhibitory effect on the metabolic activity of B. lata when exposed to the surfaces as single species.DiscussionOur results highlight the benefits of additional testing of microbial communities rather than pure cultures. These experiments allow for enhanced evaluation of antimicrobial surfaces since they also take complex and diverse interactions within a surface microbiota into account. Therefore, community testing might be the more holistic approach for the testing of antibacterial materials.